2020
DOI: 10.1136/bmjgast-2020-000401
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in gastroenterology registrars: a feasibility study conducted in the East of England using a 31-item questionnaire

Abstract: ObjectiveThe scale of burnout in UK gastroenterology trainees and the feasibility to determine its prevalence using the validated Maslach Burnout Inventory-Human Services Survey (MBI-HSS) tool are unknown. The primary objective of this region-wide pilot study was to evaluate the response rate to a 31-item questionnaire. The secondary objectives were to estimate the prevalence of burnout in gastroenterology trainees within the East of England deanery (EoE) and identify common stressors that trainees experience.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…In a recent pilot study of gastroenterology trainees in the East of England, even though 35.3% had burnout or were at high risk of burnout, 51.6% of all trainees were unaware of available mental well-being services that existed within the training programme. 6 In closing, we fully support Buscarini et al's call for better safeguards against burnout in gastroenterology. In addition, more research on burnout is also needed within the specialty.…”
supporting
confidence: 70%
“…In a recent pilot study of gastroenterology trainees in the East of England, even though 35.3% had burnout or were at high risk of burnout, 51.6% of all trainees were unaware of available mental well-being services that existed within the training programme. 6 In closing, we fully support Buscarini et al's call for better safeguards against burnout in gastroenterology. In addition, more research on burnout is also needed within the specialty.…”
supporting
confidence: 70%
“…45.5% (5/11) of studies reported that female gastroenterologists experienced more anxiety, stress or burnout than male gastroenterologists. In the remaining 6 studies, 2 studies reported no difference in burnout prevalence rates between genders(21,24), 3 studies reported lower PA scores in females(27,28,31) but did not report gender-specific burnout rates, and 1 study did not report any data on gender comparisons(29). Regardless of burnout tools or criteria of burnout, a meta-analysis of 2,694 gastroenterologists across all 6 studies that reported burnout prevalence suggested that female gastroenterologists may be at higher risk of burnout compared to their male counterparts; OR = 1.5 (95% CI: 1.1 to 2.1), p < 0.01 (Supplementary Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Work-related stressors reported by respondents will be grouped according to commonly occurring themes that have been previously identified in publications of burnout in gastroenterology. 13 20 Any discrepancies or disagreements will be resolved by focus group discussions.…”
Section: Discussionmentioning
confidence: 99%
“…However, EE was present in 57.5% and only 50% were aware of organisational mental health support services that they could turn to in times of need. 13 Similarly, this study will also probe respondents’ awareness of mental health support services within their respective organisations.…”
Section: Introductionmentioning
confidence: 99%